Complete chloroplast genome structural and phylogenetic analysis of Physostegia virginiana (L.) Benth. 1930 (Lamiaceae) - Changmei Du; Tingting Xiong; Yan Dong; Haishuo Gao; Yan Zhang; Jianhua Yue (Mitochondrial DNA. Part B. Resources)
Physostegia virginiana (L.) Benth. (1930) is an ornamental plant with great potential for landscaping application and cut-flower using in China. To explore its phylogenetic position and analyze the characteristics of its chloroplast (cp) genome, this study sequenced the whole cp genome of P. virginiana. The results revealed that the total length of the cp genome was 152,880 bp, and the lengths of the large single-copy region (LSC) and small single-copy region (SSC) were 84,428 and 17,396 bp, respectively. The lengths of the inverted repeat regions (IRa and IRb) were both 25,528 bp. The cp genome of P. virginiana contains 131 coding genes, namely, 86 protein-coding genes, 37 tRNA genes and eight rRNA genes. The total GC content of the cp genome was 38.38%. The phylogenetic results revealed that P. virginiana was closely related to Gomphostemma lucidum. The results of this study provide a molecular basis for the phylogenetic localization of P. virginiana and basic data for its identification and resource development.